The Influence of Work Environment, Work Motivation and Work Spirit on Employee Loyalty at The Adipurna Innovation Foundation Asia - Kusnadi Kusnadi; Achmad Zaky (Management Research Studies Journal, 2023)
Adipurna Foundation Asian innovation is companies operating in the field educational community platform, company This is startup companies that provide service online courses and workshops. Research objectives For analyze influence environment work , motivation work , be enthusiastic Work to loyalty employee At the Adipurna Foundation Asian Innovation Vocasia . Research methods used with population study that is all over employees at the Adipurna Foundation Asian Innovation Vocasia that is totaling 50 employees , with technique taking sample is saturated sampling Because amount the population is small , so amount sample of 50 employees . Research results show that there is influence environment Work to loyalty employee Adipurna Foundation Asian Innovation Vocasia , so environment Work capable increase loyalty employee Adipurna Foundation Asian Innovation Vocasia . Motivation and enthusiasm Work No influential to loyalty employee Spirit Work Vocasia , p This means that motivation and enthusiasm Work Work No capable increase loyalty employee Adipurna Foundation Asian Innovation Vocasia.